THE EFFECT OF INQUIRY METHOD ON PSYCOMOTOR LEARNING OUTCOMES OF CLASS XI AT SMA ALKHAIRAAT LABUHA - Herawati Herawati; Juniartin Juniartin; Lintal Muna (Media Bina Ilmiah, 2023)
The inquiry method can be used to see student psychomotor learning outcomes on plant tissue structure material. The advantages of this method provide opportunities for students to improve critical thinking patterns to be actively involved in learning, so that they are able to find answers to the problems in question. This research aims to determine the effect of inquiry method on psychomotor learning outcomes of class XI students on the material of plant tissue structure at SMA Alkhairaat Labuha, South Halmahera district. This type of research is experimental research (quasi-experimental) with quantitative research methods. Population of the research was all students of class XI Science students Alkhairaat Labuha High School and two classes were selected as samples by purposive sampling. The class selected as the research sample was class XI IPA2, which consisted of 20 students as the experimental class, and class XI IPA3 which consisted of 20 students as the control class. The instruments used in this study were psychomotor test rubrics and observation sheets. Data collection techniques used are psychomotor tests, observation, and documentation. Data were analyzed by testing the prerequisites and hypothesis testing. The results of this research indicate that based on the t-test, the tcount value is 6,905 > ttable value is 2,093, which means Ha is accepted. Thus it can be said that there is an effect of the inquiry method on the psychomotor learning outcomes of class XI science students on the material of plant tissue structure at Alkhairaat Labuha High School, South Halmahera District.